Social Forces in the Making of the New Europe - Bieler, Andreas. author. aut Link
XVIII, 261 p.
Keywords: The main argument of this book is that the revival of European integration in the mid-1980s and the emergence of a "New Europe" have to be analyzed against the background of globalization and the transnational restructuing of social forces since the early 1970s.